Crosby, Stills & Nash long time comin' - Nash, Graham, 1942-; Stills, Stephen; Crosby, David, 1941-2023 (Warner Music, 2004)
A showcase of the group's 20-plus years together with concert and TV footage, recording sessions, and interviews.